Does Strategic Planning Matter in Enhancing Performance of Zakah Organization? Some Insights from Zakah Management in Indonesia - Rahmatina Awaliah Kasri; Niken Iwani Surya Putri (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
The paper aims to explore strategic planning practices of zakah organizations in Indonesia and their impacts on the organizational performance. It uses qualitative research approach with semi-structured interviews and a quantitative approach based on financial data from the organizations. The study found several interesting findings. First, from mission statement analysis, different zakah organizations seem to have different idealized views and focus on achieving either particular organizational characteristics or organizational targets/outcomes. Second, the strategic planning processes tend to follow the “by-design” and the “by-flow” strategies which are implemented in all zakah agencies regardless of its type. However, it is notable that only the non-government zakah agencies were flexible enough to run programs based on recommendation of the zakah payers. Third, in terms of performance, it is found that corporate zakah agency has the highest collection capacity, while the private zakah agency has the highest distributional capacity. Based on the findings, it is suggested that the zakah organizations should focus on their targets/outcomes and properly design their programs. It is also argued that all zakah agency has formulated sound mission statements and it is reflected well in the organizational capacity. This implies that there is a positive relationship between strategic planning and organizational performance. Keywords: Zakat, Strategic Management, Zakah organization